Membangun Pendidikan Dasar Bernuansa Demokratis dan Hak Asasi Manusia - muaidi123; Musafir, Musafir; Mulyono, Ana; Chesy, Mias Lailuh; Aprian, Faijal Youdan; Aodiyana, Baiq Sarah Nova; Aini, Lita Zahratul; Hidayat, Lalu Rian; Irman, Irman; Akbar, Raden Habib; Fari, Deo Permata Alge; Fahmi, Reza; Ilgana, Ilham Alif; Paresa, Dende Kalia (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
The purpose of this writing is to analyze and describe efforts to build basic education that has a democratic nuance and is based on the principles of human rights (HAM). This research aims to explore how the implementation of democracy and human rights education can be implemented in the basic education curriculum, by providing equal opportunities for every child to obtain a decent education. In this discussion, the analysis focuses on two main aspects, namely student-centered learning, which allows students to play an active role in the educational process, and the application of democratic values and human rights in learning Pancasila and Citizenship Education (PPKn). The results of the analysis show that education that has a democratic nuance and is based on human rights can create an inclusive environment, respect differences, and encourage students' awareness of their rights and obligations as citizens. With this approach, it is hoped that a generation will be created that is not only intellectually intelligent, but also has high social awareness of democratic values and human rights.